Implementation Of Occupational Safety And Health (OSH) As An Effort To Prevent Work Accidents In The Production Process At PT XX - Yuono Yuono; Sherli Rahmawani Putri; Ahsha Nabila Hasna; Riny Yolandha Parapat (PT Ilmu Data Indonesia, 2026)
Occupational Safety and Health (OSH) is an essential aspect of industrial activities that contributes to the creation of a safe, healthy, and productive work environment. The high risk of workplace accidents in production processes requires companies to implement effective OSH programs to minimize potential hazards that may cause losses to both workers and the company. This study aims to analyze the implementation of Occupational Safety and Health (OSH) as an effort to prevent workplace accidents in the production process at PT XX. The research employed a descriptive qualitative method, with data collected through field observations, interviews, and document reviews. The results indicate that PT XX has implemented various OSH programs, including the use of personal protective equipment (PPE), occupational safety training, installation of safety signs, and routine inspections of production areas and work equipment. However, several challenges were still identified, such as suboptimal worker compliance with PPE usage and limited awareness of potential hazards in the workplace. The consistent implementation of OSH practices has been proven to reduce the risk of workplace accidents and support the continuity of production activities. Therefore, continuous improvement in supervision, employee guidance, and the strengthening of a safety culture are necessary to enhance the effectiveness of OSH implementation within the company.